Comparison of various assays for detection of AFP in differentiating patients with primary hepatocellular carcinoma from controls. Issue 8 (August 1980) - Chan, S H; Heng, S H; Yo, S L; Oon, C J
Abstract : Four assays for the detection of alphafetoprotein (AFP) in the diagnosis of primary hepatocellular carcinoma (HCC) were evaluated. The frequency of AFP detection was compared in 89 HCC patients and in 71 patients with chronic active hepatitis/cirrhosis. Of the four assays, immunodiffusion, counterimmunoelectrophoresis (CIE), supplement CIE, and radioimmunoassay, the best for differentiating patients with HCC from those with chronic active hepatitis and cirrhosis was CIE.